Spatial Analysis of Neurological Disorders among Pesticide-Exposed Chili Farmers in Bandungan, Semarang Regency, 2025 - Eram Tunggul Pawenang; Fitri Indrawati; Heni Isniyati (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Environmental and worker health issues causing from pesticide exposure remain a significant concern in the agricultural sector. Some research has found that longer exposure to pesticides can probably cause neurological disorders. This study aims to analyze the relationship between exposure intensity, individual characteristics, and the incidence of neurological disorders with the spatial distribution pattern in the farming region. Methods: This research is a cross-sectional study with a spatial approach were carried out involving 75 chili farmers in the Bandungan region. Information about frequency exposed to pesticides, individual characteristics, and symptoms of neurological disorder was compiled by structured questionnaires, observation and analyzed based on the Romberg test. The data was analyzed using statistical and spatial tests with Moran's Index. Results and Discussion: The data indicated that most of the farmers (at least 50%) showed symptoms of neurological problems. The highest number of cases was found among farmers who were older than 50 (66.7%), with an overweight body mass index (BMI) (80%), and incomplete use of safety equipment (59%). Autocorrelation spatial showed the result of a notable significance clustering of neurological disorders (Moran’s I Z-score = 3.94, p ≤ 0.01), with the high-risk location in Kenteng Village. Based on bivariate tests, it showed that the increase in risk of neurological disorders is influenced by increasing age, BMI, and the complete use of safety equipment. Conclusion: Therefore, efforts to promote, collaborate, and implement the use of complete PPE are needed to reduce the health risks of farmers exposed to pesticides.